Antimicrobial activity of a porphyrin binding peptide. Issue 4 (21st August 2018) - Shirley, David J.; Chrom, Christina L.; Richards, Elizabeth A.; Carone, Benjamin R.; Caputo, Gregory A.
Abstract: Amphiphilic alpha‐helices are common motifs used in numerous biological systems including membrane channels/pores and antimicrobial peptides (AMPs), and binding proteins, and a variety of synthetic biomaterials. Previously, an amphiphilic peptide with lysine‐containing motifs was shown to reversibly bind the anionic porphyrin meso‐Tetra(4‐sulfonatophenyl)porphyrin ( TPPS 4 2 − ) and promote the formation of excitonically coupled conductive J‐aggregates. The work presented here focuses on the use of this amphiphilic peptide and derivatives as a potential antimicrobial agent. AMPs are naturally occurring components of the innate immune system, which selectively target and kill bacteria. Sequence derivatives were synthesized in which the position of the Trp, used as a fluorescence reporter, was changed. Additional variants were synthesized where the hydrophobic amino acids were replaced with Ala to reduce net hydrophobicity or where the cationic Lys residues were replaced with diaminopropionic acid (Dap). All peptide sequences retained the ability to bind TPPS 4 2 − and promote the formation of J‐aggregates. The peptides all exhibited a preference for binding anionic lipid vesicles compared to zwitterionic bilayers. The Trp position did not impact antimicrobial activity, but the substituted peptides exhibited markedly lower efficacy. The Dap‐containing peptide was only active against E. coli and P. aeruginosa, while the Ala‐substituted peptide was inactive at the concentrations tested. This trend was also evident in bacterial membrane permeabilization. The results indicate that the amphiphilic porphyrin binding peptides can also be used as antimicrobial peptides. The cationic nature is a driver in binding to lipid bilayers, but the overall hydrophobicity is important for antimicrobial activity and membrane disruption. Abstract :